Correlating the role of hydrophilic/hydrophobic nature of Rh(I) and Ru(II) supported organosilica/silica catalysts in organotransformation reactions - Lazar, Anish; George, Shoy C.; Jithesh, P. R.; Vinod, C. P.; Singh, A. P. (Applied Catalysis A-General, 2016)
Highly reactive and hydrophobic triphenyl phosphine based rhodium(I) and ruthenium(II) organometallic complexes over benzene containing periodic mesoporous organosilica (PMOB) have been synthesized. This has been achieved by the immobilization of neat metal complexes like RhCl(PPh3)(3) [Wilkinson catalyst], RuHCl(CO)(PPh3)(3) and RuCl2(PPh3)(3) over aminofunctionalized PMOB to get RhCl(PPh3)(2)-PrNH2PMOB, RuHCl(CO)(PPh3)(2)-PrNH2PMOB and RuCl2(PPh3)(3)-PrNH2PMOB, respectively. The physico-chemical properties of the functionalized catalysts were analyzed by elemental analysis, ICP-OES, XRD, N-2 sorption analyses, FT-IR, solid state C-13 and Si-29 NMR spectra, XPS, SEM, TEM and contact angle measurements. The XRD and N-2 sorption analyses showed excellent textural properties with ordered mesoporous channel structure of all synthesized catalysts. The organic moieties anchored in PMOB were confirmed by C-13 CPMAS NMR and Fr-IR spectroscopy with Si-29 CPMAS NMR spectroscopy providing the information about the degree of functionalization of surface silanol groups with organic moiety. The Rh(I) and Ru(II) complexes supported on MCM-41/SBA-15/PMOE (ethane-PMO) were synthesized, and their catalytic activities in hydrogenation and sulfoxidation reactions were compared with Rh(I) and Ru(II) complexes supported on PMOB. The results show that PMOB based catalysts exhibit higher activities and selectivities than MCM-41/SBA-15/PMOB supported catalysts, neat homogeneous complexes and without catalyst. The better catalytic performance of PMOB based catalyst is attributed to the hydrophobic nature and high surface area of the PMOB support. The recycling studies of anchored catalysts show no major deactivation of the catalyst. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Heterogeneous catalysts; Hydrogenation and sulfoxidation; Hydrophobic; Periodic mesoporous organosilica

Hydrophobic WO3/SiO2 catalyst for the nitration of aromatics in liquid phase - Kulal, A. B.; Kasabe, M. M.; Jadhav, P. V.; Dongare, M. K.; Umbarkar, S. B. (Applied Catalysis A-General, 2019)
WO3/SiO2 solid acid catalyst synthesized using sol gel method has shown promising activity (up to 65% conversion) for aromatic nitration in liquid phase using commercial nitric acid (70%) as nitrating agent without using any sulfuric acid. The water formed during the reaction as well as water from dilute nitric acid (70%) was removed azeotropically, however due to the hydrophilic nature of the catalyst, some water gets strongly adsorbed on catalyst surface forming a barrier layer between catalyst and organics. This prevents effective adsorption of substrate on catalyst surface for its subsequent reaction. To improve the activity further, the hydrophilic/hydrophobic nature of the catalyst was altered by post modification by grafting with commercial short chain organosilane (Dynasylan 9896). The modified 20% WO3/SiO2 catalyst when used for o-xylene nitration in liquid phase, showed significant increase in the conversion from 65% to 80% under identical reaction conditions. Catalyst characterization revealed decrease in the surface area of 20% WO3/SiO2 from 356 m(2)/g to 302 m(2)/g after grafting with Dynasylan 9896. The fine dispersion of WO3 particles (2-5 run) on silica support was not affected due to modification. NMR and FTIR study revealed the decrease in surface hydroxyl groups imparting hydrophobicity to the catalyst. Interestingly the total acidic sites of the catalyst remained almost unaltered (0.54 mmol NH3/g) even after modification. Even though, the acidity and other characteristics of the catalyst did not change appreciably, there was a considerable increase in the o-xylene conversion which can be ascribed to the hydrophobic nature of the catalyst.
Keywords: Aromatic nitration; grafting; heterogeneous catalysis; Hydrophobic; Sol-gel synthesis

LHRH-conjugated, PEGylated, poly-lactide-co-glycolide nanocapsules for targeted delivery of combinational chemotherapeutic drugs Docetaxel and Quercetin for prostate cancer - Shitole, Ajinkya A.; Sharma, Neeti; Giram, Prabhanjan; Khandwekar, Anand; Baruah, Meghna; Garnaik, Baijayantimala; Koratkar, Santosh (Materials Science & Engineering C-Materials for Biological Applications, 2020)
One of the major challenges in effective cancer chemotherapy is the severe systemic cytotoxicities of anticancer drugs on healthy tissues. The present study reports chemically modified polymeric nanocapsules (NCs) encapsulating combination of chemotherapeutic drugs Docetaxel (DTX) and Quercetin (QU) for its active targeting to prostate cancer (PCa). The active targeting was achieved by conjugating Luteinizing-hormone-releasing hormone (LHRH) ligand to poly-lactide-co-glycolide (PLGA) using polyethylene glycol (PEG) as a spacer. The structure of the conjugates was characterized and confirmed using H-1 NMR and ATR-FTIR. The drug encapsulated NCs showed a homogenous size distribution with their size ranging between 120 and 150 nm, and exhibited a negative zeta potential in the range of - 20 to - 40 mV. The in vitro release studies highlighted the sustained drug release pattern from the respective NCs; while the PEG coating to polymeric NCs provided serum stability to the NCs. The in vitro biological evaluation of the NCs was conducted using PC-3 and LNCaP cell lines. The results of the cellular uptake studies showed a significantly higher untake of the LHRH targeted NCs, while the LHRH-targeted-PEGylated DTX: QU NCs exhibited higher caspase-3 activity. The cell viability assay results showed the enhanced cell inhibition activity of the combinatorial DTX: QU when compared to individual DTX. Further, higher cell cytotoxicity was achieved by LHRH-targeted DTX: QU NCs as compared to their free-form or non-targeted NCs. Finally, the results of in vivo tumor localization and in vivo antitumor activity studies complimented and upheld the in vitro results, demonstrating the beneficial role of PLGA-PEG-LHRH NCs encapsulating combination of DTX and QU in combating prostate cancer (PCa).
Keywords: Active targeting; Anticancer; Controlled release; EPR effect; Hydrophobic; Prostate

Tailoring of rheological properties through hydrophobic interactions in silica-based liquid crystal gels - Sumana, S.; Chakrabortty, Pratyasha; Karumuthil, Subash Cherumannil; Prasad, S. Krishna; Prasad, Bhagavatula L. V. (ChemPhysChem, 2025)
Modification of the intrinsic hydrophilic character of the pristine silica nanoparticles (SiNP) decorated with silanol moieties into a hydrophobic state has been of substantial interest, owing to the amenability to gelation of desirable liquids. Many reports exist on composites of SiNP with liquid crystals (LCs), an epitome of anisotropic soft matter. The fumed SiNP, unlike its precipitated counterpart, has been the preferred variety. A family of colloidal gel systems is reported, consisting of precipitated SiNP in a nematic LC, formed by substituting some native silanols with methyl, butyl, or dodecane chains. Detailed steady state and oscillatory rheological measurements are performed, along with analyses using the soft glass and other viscoelastic models. The study demonstrates that the sophisticated modified fractional models, Kelvin-Voight and Maxwell, proposed for generalized viscoelastic behavior of soft materials, are quite successful in describing these nematic gels as well. The observed nontrivial relationship between the ligand length and the strength of the gel network is elucidated on the basis of a judicious combination of the van der Waals, hydrogen bonding, and hydrophobic interactions, leading to a detailed understanding of the viscoelastic behavior of the composites and the influence of SiNP surface chemistry.
Keywords: fractional viscoelastic models; Hydrophobic; nematic; rheological studies; silica nanoparticles

Eco-friendly gradient porous poly(3-hydroxybutyrate)/natural fiber aerogels for highly efficient thermo-acoustic insulation - Akhila, N. S.; Shrishti, S. K.; Suresh, Sruthi; Torris, Arun; Gowd, E. Bhoje (ACS Applied Polymer Materials, 2026)
The urgent demand for lightweight thermo-acoustic insulation (TAI) materials in transportation and building infrastructure is constrained by difficulties in synthesis and environmental concerns about nondegradable materials. In this study, a strategy is proposed to create gradient porous, biodegradable, fibrillar aerogels via layer-by-layer casting with poly(3-hydroxybutyrate) (PHB), banana fibers (BF), and cellulose nanofibers (CNFs), followed by unidirectional freezing and freeze-drying. These gradient porous aerogels possess a hierarchical porous structure, ensuring excellent hydrophobicity, mechanical strength, and thermal dimensional stability, and exhibit excellent acoustic insulation performance due to impedance mismatch and pore-neck resonance effects, achieving a noise reduction coefficient (NRC) of 0.60. The gradient-structure-based aerogels also exhibit better thermal insulation performance, with ultralow thermal conductivities as low as 0.03 W/(m & centerdot;K). The flame-retardant properties are significantly enhanced by incorporating Al(OH)3 via a solvent-exchange method, thereby achieving a limiting oxygen index (LOI) of 29.3%. The lightweight, gradient-structure-based, biodegradable aerogels possess excellent thermo-acoustic insulation and flame-retardant properties, thereby offering great promise as sustainable insulation materials for next-generation building infrastructure.
Keywords: acousticinsulation; aerogels; biodegradable; flame retardancy; Hydrophobic; poly(3-hydroxybutyrate); Thermal insulation